Tracing the Path to Universal Banking: The Indian Scenario - Goswami, Chandana; Deb, Nilanjana (Journal of Nepalese Business Studies, 2012)
In India, the Commercial Banking sector has been the dominant element in the country’s financial system and performed the key functions of providing liquidity and payment services to the real sector, and has accounted for bulk of the financial intermediation process. However, since early 1990s, the Indian banking sector has been subjected to various reform measures initiated by the Government at the backdrop of economy-wide structural adjustment programme and also in response to the unsatisfactory economic and qualitative performance of the Public Sector Banks owing to lack of competition, low capital base, low productivity and high intermediation cost. Financial sector reforms have uprooted many of the outdated regulatory fences within which banks were required to carry out their activities. This provided more liberty to banks and they started exploiting different areas of operation. Gradually, many of the banks, apart from their indigenous function i.e., banking, started having substantial interests in all sorts of financial businesses like insurance, funds management, mutual funds, securities trading etc. Eventually, such a bank acquired the status of Financial Conglomerate and slowly began moving towards Universal Banking framework. However, in this process, the risk exposure of banks increased further and also it has raised a question on what should be the effective regulatory system for monitoring such conglomerates. Therefore, an attempt is made to trace the path of transition of Indian banks towards Universal banking framework, their risk exposure, opportunities and challenges confronted in this process of transition and the regulatory system needed to monitor such entities. The Journal of Nepalese Business Studies Vol. Vii, No. 1, 2010-2011 Page : 17-30 Uploaded date: July 7, 2012